Molecular Mechanisms of Curcumin Renoprotection in Experimental Acute Renal Injury - Fan, Youling; Chen, Hongtao; Peng, Huihua; Huang, Fang; Zhong, Jiying; Zhou, Jun (Frontiers in Pharmacology, 2017)
As a highly perfused organ, the kidney is especially sensitive to ischemia and reperfusion. Ischemia-reperfusion (IR)-induced acute kidney injury (AKI) has a high incidence during the perioperative period in the clinic and is an important link in ischemic acute renal failure (IARF). Therefore, IR-induced AKI has important clinical significance and it is necessary to explore to develop drugs to prevent and alleviate IR-induced AKI. Curcumin [diferuloylmethane, 1,7-bis(4-hydroxy-3-methoxiphenyl)-1,6-heptadiene-3,5-dione)] is a polyphenol compound derived from Curcuma longa (turmeric) and was shown to have a renoprotective effect on ischemia-reperfusion injury (IRI) in a previous study. However, the specific mechanisms underlying the protective role of curcumin in IR-induced AKI are not completely understood. APPL1 is a protein coding gene that has been shown to be involved in the crosstalk between the adiponectin-signaling and insulin-signaling pathways. In the study, to investigate the molecular mechanisms of curcumin effects in kidney ischemia/reperfusion model, we observed the effect of curcumin in experimental models of IR-induced AKI and we found that curcumin treatment significantly increased the expression of APPL1 and inhibited the activation of Akt after IR treatment in the kidney. Our in vitro results showed that apoptosis of renal tubular epithelial cells was exacerbated with hypoxia-reoxygenation (HR) treatment compared to sham control cells. Curcumin significantly decreased the rate of apoptosis in renal tubular epithelial cells with HR treatment. Moreover, knockdown of APPL1 activated Akt and subsequently aggravated apoptosis in HR-treated renal tubular epithelial cells. Conversely, inhibition of Akt directly reversed the effects of APPL1 knockdown. In summary, our study demonstrated that curcumin mediated upregulation of APPL1 protects against ischemia reperfusion induced AKI by inhibiting Akt phosphorylation.